The development of management accounting skills in situations where practical exposure is limited: The perceptions of training officers in South Africa - Bishop, W.A. (South African Journal of Higher Education, 2019)
Training office auditing firms in South Africa are required by the South African Institute of Chartered Accountants (SAICA) training regulations to provide basic exposure to trainees in management accounting. The purpose of this paper was to determine (1) the ways in which large, medium-sized and small training office auditing firms in South Africa evaluate the competency of trainee accountants in the field of management accounting, (2) to what extent alternative skills transfer methods are used and (3) the perceptions of training officers of the use of simulation as a skills transfer method. A web-based questionnaire was used. This study showed that simulated training, either in-house, outsourced or a combination of the two, is actively used by a number of training office auditing firms in South Africa in order to assess competency in the field of management accounting where practical exposure through performing actual tasks is limited. The study also revealed that training officers perceive simulation to be effective in the assessment of competency in management accounting residual skills competency areas. The research is valuable to SAICA and training office auditing firms, as it provides an overview of how skills in management accounting are transferred to trainee accountants.